DETERMINAN KEMANDIRIAN KEUANGAN DAERAH PEMERINTAH PROVINSI DI PULAU SUMATERA - Aini, Siti Nurul; Sulaiman, Sulaiman; Aprianti, Siska (Politeknik Negeri Ambon, 2025)
Introduction: Regional financial “independence is an essential indicator in measuring the ability of local governments to finance government implementation and development independently without relying on transfer funds from the central government. In the province of Sumatra Island, achieving financial independence remains a challenge due to a significant reliance on balance funds. This research aims to analyse the effect of the Balance, Capital Expenditure, Leverage, and Government Size Fund on regional financial independence in 10 provinces on Sumatra Island during the 2019-2023 period. Methods: The method used is quantitative research with panel data, analysed using the Fixed Effects Model (FEM) in E-Views 13.Results: Research indicates that the Balance Fund significantly adversely affects regional financial independence, suggesting that dependence on central funds reduces fiscal autonomy. On the other hand, Capital Expenditure has a significant positive influence, suggesting that local governments' investment in productive asset development can foster greater budgetary independence. The government's leverage and size variables did not have a significant effect, indicating the need to improve debt and asset management to impact regional financial independence positively. The discussion of the results links these findings to agency theory, highlighting the conflict of incentives between central and local governments and the importance of proper incentives to promote fiscal independence.” This study concluded that strengthening local revenue and optimising capital expenditure are the primary keys to increasing regional financial independence on Sumatra Island. Keywords: Regional Financial Independence, Balanced Fund, Capital Expenditure, Leverage, Agency Theory